Genetic determinants of myocardial electric instability in patients with coronary heart disease undergoing endovascular intervention - Yu. I. Afanasiev; A. V. Kuzubova; S. Yu. Grigorova (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To assess the role of genetic factors in coronary atherosclerosis progression and myocardial electric instability development among patients with coronary heart disease (CHD) undergoing endovascular interventions. Material and methods. The main group (MG) included 97 CHD patients (mean age 53,6±7,8 years), who underwent endovascular revascularization. The assessed parameters included genetic polymorphisms of haptoglobin (Hp), C´3 complement component (C´3), vitamin D-binding protein (Gc), and transferrin (Tf), as well as immune inflammation markers (interleukin-6, tumor necrosis factor-α, and C-reactive protein, CRP) and electrocardiographic QT interval dispersion. The control group (CG) included 100 healthy donors (mean age 47,0±8,6 years).Results. In MG patients, compared to controls, there was a significant increase in QT interval dispersion. The extent of QT interval dispersion reduction after endovascular coronary stenting was maximal in patients with one or two lesions. At early post-intervention stages, immune inflammation processes intensified. The severity of coronary atherosclerosis affected the correlation between CRP levels and QT interval dispersion. QT dispersion parameters were associated with Hp 2–2, С´3 SS, Gc 1–1, and Tf CC. In С´3-SS-positive patients, there was a positive correlation between CRP levels and QT interval dispersion (QTd). Conclusion. The results obtained confirm the important role of genetic factors in the immune inflammation activation among CHD patients. After endovascular intervention, immune inflammation is associated with atherosclerosis progression and myocardial electrical instability